System Integration of Finger Contracture Prevention System Device for Early Post Stroke Rehabilitation - Ahmad, Ahmad; Nor Azmi Ab Patar, Mohd; P.P. Abdul Majeed, Anwar; Lee, Hokyoo; Mahmud, Jamaluddin (International Journal of Engineering and Technology, 2018)
Physical rehabilitation is the key for recovering motor control and function for patients with neurological disorders. Conventional therapy procedures tend to be labor intensive and non-standardized, especially in the area of hand and finger rehabilitation. Robotics technology offers a way to reduce the burden of the physiotherapists in a repeatable and measurable manner. This work describes a novel finger rehabilitation approach for hand motor functions recovery targeting early acute stroke survivors using an active exoskeleton robotic device. The device is designed based on anthropometric measurement data of hand ergonomics. The device is able to assist the subject in performing flexion and extension movements. The main specification of the device includes a differential system with a current sensing element and a lead screw mechanism which allows for the self-governing movement of each finger through the usage of small actuators. The device is safe, easy to deploy, integrated with sensing element and offers multiple training possibilities. Moreover, it has been observed that the device could offer an objective evaluation of the patientsâ€™ motor function activity, suggesting its potentiality for a customized home-based therapy program for patients.Â Â